2013
DOI: 10.4103/0257-7941.131973
|View full text |Cite
|
Sign up to set email alerts
|

Lemongrass essential oil gel as a local drug delivery agent for the treatment of periodontitis

Abstract: Background:It has been long recognized that periodontal diseases are infections of the periodontium, comprising the bacterial etiology, an immune response, and tissue destruction. Treatment strategies aiming primarily at suppressing or eliminating specific periodontal pathogens include adjunct use of local and systemic antibiotics as part of nonsurgical periodontal therapy. Unwanted side effects and resistance of microorganisms toward antibiotics due to their widespread use have modified the general perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…Studies such as Warad et al 25 (2013) and Mandras et al 27 (2016) reported excellent therapeutic properties of essential oils in a variety of aerobic, anaerobic and fungal microorganisms. In our study we used Lt as the herbal medicine of choice; Lt is a native species of Brazilian vegetation, popularly used to treat various pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies such as Warad et al 25 (2013) and Mandras et al 27 (2016) reported excellent therapeutic properties of essential oils in a variety of aerobic, anaerobic and fungal microorganisms. In our study we used Lt as the herbal medicine of choice; Lt is a native species of Brazilian vegetation, popularly used to treat various pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to resolve such complications and promote more effective and less harmful treatment, different therapeutic alternatives may be tested such as the herbal medicine [25][26][27][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining local delivery antibiotic agents with scaling and root planning became needed to achieve the periodontal therapy goal as reduction periodontal pocket depth and gaining clinical attachment level. Many commercial local delivery antimicrobial agents are available, but the demand for inexpensive, safe, and effective agents has encouraged the use of natural extracts (28) . In this study, we used 2% concentration of lemongrass essential oil gel as an adjunct to the conventional therapy of moderate periodontitis.…”
Section: Discussionmentioning
confidence: 99%